Geochemical characteristics of rare earth elements in late Palaeozoic coals from North China - Wen, Long; Huang, Wenhui; Zhang, Yuanfu; Jiu, Bo (Frontiers in Earth Science, 2024)
Introduction: China is a large country of REE resources and production, supplying more than 90% of the world’s rare earth consumption market, China’s traditional REE resources, although rich, but reserves are also declining, in recent years, scholars have shown that the REEs in the specific geological conditions in the coals can be enriched, and even reach the industrial grade, the search for more REE mineral resources will be of great strategic significance. Methods: The article has selected the Zibo, Taozao, Huainan, Datong, Huozhou, Jungar, and Weibei coalfields in North China as the research objects. Based on inductively coupled plasma mass spectrometry (ICP-MS) analyses, the study provides a detailed analysis of the enrichment rules and distribution patterns of rare earth elements (REEs) in coal under different geological conditions. Results: The REE distribution patterns in Late Palaeozoic coals in North China are characterized by enrichment of LREEs, deficit of HREEs with gentle changes, and obvious negative anomalies of Eu, the enrichment of REE in coal is controlled by provenance and volcanism, and is related to distance of transport terrigenous material and the sedimentary environment. The REEs concentrations in North China indicates that Late Palaeozoic coals in the mining areas of the north, northwest, and western parts of North China are significantly enriched in REEs. In addition, REEs in Late Palaeozoic coals in the southeastern mining areas are relatively enriched, and the central and eastern regions are significantly depleted. Discussion: Large coal-type rare earth deposits are expected to be developed in North China, particularly the Datong coalfield, Jungar coal mine and the Weibei coal mine in the eastern margin of the Ordos Basin, and the Zibo coalfield.